1995
DOI: 10.1007/bf02415386
|View full text |Cite
|
Sign up to set email alerts
|

Subcritical cascade liquid-salt reactor as an element of the fuel cycle

Abstract: Large-scale development of nuclear power is pointless if there is no long-term future for it and if it cannot meet the requirements that are predicted for the future. There is still no serious competitor for nuclear power in the long-term future, besides thermonuclear power, which must still prove to be economical and efficient, not only in the variant of purely thermonuclear power but also in a hybrid variant with subcritical blankets. This has not yet been demonstrated, and the possibility of nuclear power, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…It has been suggested that the principle of cascade multiplication of neutrons in two-section blankets be used to decrease the power requirements of the driving accelerator [6,7].…”
mentioning
confidence: 99%
“…It has been suggested that the principle of cascade multiplication of neutrons in two-section blankets be used to decrease the power requirements of the driving accelerator [6,7].…”
mentioning
confidence: 99%